The first year of the COVID-19 pandemic in nursing homes: a meta-analysis study - Sungur, Sevda; Metintaş, Selma; Kılınç, Ali; Oktar, Didem; Önsüz, Muhammed Fatih (International Journal of Research in Medical Sciences, 2023)
Severe impact of COVID-19 on nursing homes and the morbidity and mortality rates in nursing home residents can be higher than in the community during a pandemic. This study aimed to meta-analyse the COVID-19 attack, fatality and mortality rates among nursing home residents and to meta-analyse the risk ratio values by comparing these rates with those of the countries in which the nursing homes are located. The data was obtained from COVID-19 attack, mortality, and fatality rates of nursing home residents. Additional meta-analysis was performed using risk ratio calculated by dividing the data obtained from nursing homes by the expected numbers calculated using case, death, and population data from COVID-19. A total of 6,758,241 COVID-19 patients from 8 different countries and 19 studies were included during the meta-analysis study period. In nursing home residents compared to the general population, the risk ratio (95%CI) for COVID-19 attack rate was 148.19 (99.45 to 220.82), the mortality rate was 341.16 (211.94 to 549.15), and the fatality rate was 2.36 (1.90 to 2.93) (each p<0.001). A meta-analysis of well-documented studies has shown that community morbidity and mortality rates can reach higher levels compared to community during a pandemic. Finding the exact causes can only be achieved after adjusting nursing home infection rates with regional rates. To ensure better community management of the COVID-19 pandemic and prevent future pandemics, preventive measures should be taken earlier.